Neonatal neuronal WWOX gene therapy rescues Wwox null phenotypes - Srinivasarao Repudi; Irina Kustanovich; Sara Abu‐Swai; Shani Stern; Rami I Aqeilan (EMBO Molecular Medicine)
Abstract WW domain‐containing oxidoreductase (WWOX) is an emerging neural gene‐regulating homeostasis of the central nervous system. Germline biallelic mutations in WWOX cause WWOX‐related epileptic encephalopathy (WOREE) syndrome and spinocerebellar ataxia and autosomal recessive 12 (SCAR12), two devastating neurodevelopmental disorders with highly heterogenous clinical outcomes, the most common being severe epileptic encephalopathy and profound global developmental delay. We recently demonstrated that neuronal ablation of murine Wwox recapitulates phenotypes of Wwox‐null mice leading to intractable epilepsy, hypomyelination, and postnatal lethality. Here, we designed and produced an adeno‐associated viral vector (AAV9) harboring murine Wwox or human WWOX cDNA and driven by the human neuronal Synapsin I promoter (AAV‐SynI‐WWOX). Testing the efficacy of AAV‐SynI‐WWOX delivery in Wwox‐null mice demonstrated that specific neuronal restoration of WWOX expression rescued brain hyperexcitability and seizures, hypoglycemia, myelination deficits, and the premature lethality and behavioral deficits of Wwox‐null mice. These findings provide a proof‐of‐concept for WWOX gene therapy as a promising approach to curing children with WOREE and SCAR12.